Saussurea sagittifolia (Asteraceae, Cardueae), a new species from the Bashan Mountains region of China - Xu, Lian-Sheng; Yi, Si-Yong; Chen, You-Sheng (Phytotaxa, 2020)
Saussurea sagittifolia (Asteraceae, Cardueae), a new species from the Bashan Mountains region in China, is described and illustrated. This species belongs to Saussurea subg. Saussurea sect. Rosulescentes and is similar to S. oligocephala, but differs by its basal leaves triangular-ovate, margin with 8–15 pairs of small sharp teeth, apex acuminate, base with auricular protrusion (vs. basal leaves ovate to obovate-elliptic, margin sinuate or coarsely dentate, apex acute to obtuse, base cuneate-attenuate), cauline leaves more than 10, triangular, lanceolate, linear to subulate (vs. cauline leaves 2–4, linear).